Pengaruh lama usaha, modal usaha dan inovasi terhadap pendapatan UMKM kuliner di Kecamatan Medan Sunggal - Pratama, Rizky; Ramadhan, Anggia; Hasanah, Uswatun (Journal of Economics Research and Policy Studies, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are productive businesses managed by individuals or sole proprietorships with a certain amount of capital. With strategies created by MSME actors, these businesses can compete more effectively to become more competitive in their market. This study aims to analyze the influence of Business Duration, Business Capital, and Innovation on the Income of Culinary MSMEs. The study focuses on MSMEs in Medan Sunggal District, with a selected population of 326 culinary business operators in the Medan Sunggal area and a sample size of 77 respondents. The study utilizes primary and secondary data, employing data collection techniques that include interviews, observations, and the distribution of questionnaires to respondents/MSME operators. The data analysis technique employed was multiple linear regression. The results of the study indicate that, to some extent, the business capital variable significantly influences the income of culinary SMEs in Medan Sunggal District. However, the business duration and innovation variables do not significantly influence the income of SMEs in Medan Sunggal District.